The Syntax of the Genitive Case in Longus’ Novel Daphnis and Chloe - Chakal, Inesa (Masyarakat Linguistik Indonesia Universitas Andalas, 2024)
This study aims to explore the syntactic functions and characteristics of the genitive case in the ancient Greek novel “Daphnis and Chloe” by Longus, a text from the 2nd century AD, which exemplifies the “second sophistic” period of rhetorical development. The primary source for this research is the text of “Daphnis and Chloe”, which has been thoroughly analysed to ascertain the usage of the genitive case in various syntactic roles. The research employs descriptive and structural methods of linguistic analysis. The descriptive method identifies and explains instances of the genitive case within the text, while the structural method examines the relationships between these instances and other linguistic elements. The genitive case in the novel is found to perform multiple syntactic functions, including controlling verbs, nouns, adjectives, and expressing various semantic nuances. Detailed examples are provided to illustrate these functions and their impact on the text’s meaning. The findings offer a foundation for further studies of the genitive case in ancient Greek texts, providing significant insights for researchers and linguists interested in ancient Greek grammar and its syntactic constructions. The study enhances understanding of ancient rhetorical techniques and their application in literary texts during the “second sophistic” period.